METODE GROUNDED THEORY DALAM RISET KUALITATIF - Budiasih, I Gusti Ayu Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis, 2013)
ABSTRACT This article discusses how the grounded theory method is applied in a qualitative research. Qualitative research using grounded theory method starts from the data to achieve a theory, it does not begin with theory nor test a theory, therefore a grounded theory research requires numerous well-planned and systematic steps or procedures. Qualitative research procedure using the grounded theory method consists of several steps: 1) problem formulation stage, 2) theoretical overview usage stage (if necessary), 3) data collection and sampling stage, 4) data analysis stage, and 5) conclusion and report writing stage. Nevertheless, those five stages of grounded theory research occur simultaneously. Researcher observes, collects, and organizes data and constructs theory from data at the same time. One important technique in grounded theory research is constant (fixed) comparison process in which every data is compared to all other data one by one. Data can be collected through interviews, observation, recording, or combination of these methods. Quality of grounded theory research is largely determined on a well, correct, and disciplined execution of those steps. Keywords: grounded theory, qualitative research